Cultural Dialogue Through literature : The Implications of Homi Bhabha’s Theory of Hybridity in the Literature Class - Bellour, Leila (جامعة القدس المفتوحة, 2016)
يدرس المقال نظرية الهجنة الثقافية لهومي بابا وآثارها في قراءة النصوص الأدبية الغربية التي لا تخلو من الإمبريالية والهيمنة. إن عملية القراءة تتضمن نوعا من هذه الهجنة الثقافية. حيث أن استخلاص القارئ للمعنى يتجاوز الثنائيات المتضادة نحن/ هم، والأنا/ الآخر، والمستعمر/ المستعمر. النص في حد ذاته عالم هجين وفسيفسائي ومتعدد المشارب. إن معناه يستنبط من خلال التداخل بين ثقافة الطالب وثقافة الأديب. إن هذا الالتقاء بين الثقافات ينتج عنه عالم (لما بين) الذي يسمى بالفضاء الثالث، والذي يتجاوز الثنائيات. إن الهوية الثقافية للطالب ومعنى النص الأدبي كلاهما يتموقع في (لما بين). ويوضح هذا المقال خاصة خطر التبعية الثقافية العمياء عند قراءة نظريات الهجنة الثقافية.
The present paper aspires to vindicate Homi Bhabha’s theorization of cultural hybridity and its implications in reading Western literary texts, which are not immune from imperialism and hegemony. The act of reading is a process of cultural hybridity in which the student’s negotiation of meaning transcends the Manichean polarities us/them, Self/Other, colonizer/Colonized. The text itself is a hybrid, nomadic, and ryizomatic world where meaning is generated out of the transaction between the student’s culture and that of the author. The intercultural encounter results in a liminal space, which is also dubbed Third Space or interstice, which prevails over dichotomies. The student’s cultural identity and the text’s meaning are both located in the in-between. Of outmost significance, the paper evinces the threat of cultural assimilation when reading the theories of cultural hybridity.
Keywords: الحوار الثقافي; صراع الثقافات; الهجنة الثقافية